1995
DOI: 10.1200/jco.1995.13.6.1493
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of neoadjuvant cisplatin and fluorouracil versus carboplatin and fluorouracil in patients with stage IV-M0 head and neck cancer.

Abstract: Our results indicate that CDDP-FU is more effective than CBDCA-FU as neoadjuvant treatment in stage IV-M0 head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 26 publications
0
33
1
Order By: Relevance
“…Two prospective studies compared the effects of cisplatin and carboplatin. Both studies demonstrated advantages for cisplatin over carboplatin [59, 60]. However, the settings in both studies substantially differed from our study.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Two prospective studies compared the effects of cisplatin and carboplatin. Both studies demonstrated advantages for cisplatin over carboplatin [59, 60]. However, the settings in both studies substantially differed from our study.…”
Section: Discussioncontrasting
confidence: 62%
“…The other study found a significantly higher response rate for patients with different head and neck tumors treated with cisplatin in comparison to carboplatin. However, the CT was administered as an induction CT and not concomitant [59]. A prospective randomized trial comparing the effects in a concomitant setting with RT is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin exhibits less nephrotoxicity and no ototoxicity and is often used as an alternative for cisplatin (7). Cisplatin has demonstrated superior activity over carboplatin in several studies of patients with squamous cell carcinoma of the head and neck (SCCHN) and bladder cancer (8)(9)(10)(11)(12). A meta-analysis of randomized trials comparing cisplatin versus carboplatin-based therapy in patients with bladder cancer demonstrated that cisplatin-based therapy significantly improved complete response and overall response compared with carboplatin (13).…”
Section: Introductionmentioning
confidence: 99%
“…Carboplatin seems to be less active than cisplatin in different schedules in head and neck carcinoma [34], and its combined use with paclitaxel in cervical cancer is still under investigation [35]. Undoubtedly, we experienced a high rate (77%) of local recurrences, even in patients with negative margins, but we also reported a high percentage of surviving patients (55%) with no evidence of disease at a median of 40 months after surgery.…”
Section: Discussionmentioning
confidence: 95%